Estudo da estabilidade de polpas de frutas tropicais mistas congeladas utilizadas na formulação de bebidas - CARVALHO, Ana Vânia (Instituto de Tecnologia de Alimentos, 2019)
The aim of this study was evaluate two formulations of mixed tropical fruit pulps stored frozen (–18 °C) for 365 days as from the mixed tropical juices obtained from them: F1 - mixed tropical juice of acerola (10%), pineapple (20%), acai (5%), cashew (5%), yellow mombin (5%), camu-camu (5%), water (43.1%) and sucrose (6.9%); and F2 - mixed tropical juice of acerola (10%), pineapple (20%), acai (10%), yellow mombin (10%), water (43.4%) and sucrose (6.6%). Physical and chemical analyses and the antioxidant capacity were determined every 45 days. The tropical juices obtained were suitable in terms of current legislation referring to acidity and soluble solids. With respect to the presence of bioactive constituents, the mixed tropical juice with the highest concentrations of acai and yellow mombin showed the highest levels of total anthocyanins and total carotenoids. After 365 days of frozen storage, the losses of carotenoid contents were 2.80% for formulation F1 and 10.07% for formulation F2. As for the total anthocyanins, the losses were higher, 44.35% and 73.48% for formulations F1 and F2, respectively. In general, it was observed that frozen storage was effective in maintaining the chemical characteristics and antioxidant activity of the mixed fruit pulps studied, resulting, after defrosting and the addition of water and sucrose, in mixed tropical juices with good nutritional and functional quality.